PHP and MySQL create-modify-reuse - Boronczyk, Tim, 1979- (Create-modify-reuse guides., 2008)
* Step-by-step instructions walk readers through real-world applications. * Packed with ready-to-use projects for PHP and MySQL, this book guides readers through several real-world projects that are complete, tested, and ready to be implemented, so that readers can learn by doing. * Clearly explains to readers all aspects of design, such as portability, design flow, and integration, and shows them how to properly secure their applications for real-world implementation. * Authored by a PHP expert who is in tune with common tasks and the various problems faced by developers in everyday circumsta.